Structural and functional properties of the Kunitz-type and C-terminal domains of Amblyomin-X supporting its antitumor activity - Morais, K. L. P.; Ciccone, L.; Stura, E.; Alvarez-Flores, M. P.; Mourier, G.; Driessche, M. Vanden; Sciani, J. M.; Iqbal, A.; Kalil, S. P.; Pereira, G. J.; Marques-Porto, R.; Cunegundes, P.; et al. (Frontiers in Molecular Biosciences, 2023)
Amblyomin-X is a Kunitz-type FXa inhibitor identified through the transcriptome analysis of the salivary gland from Amblyomma sculptum tick. This protein consists of two domains of equivalent size, triggers apoptosis in different tumor cell lines, and promotes regression of tumor growth, and reduction of metastasis. To study the structural properties and functional roles of the N-terminal (N-ter) and C-terminal (C-ter) domains of Amblyomin-X, we synthesized them by solid-phase peptide synthesis, solved the X-Ray crystallographic structure of the N-ter domain, confirming its Kunitz-type signature, and studied their biological properties. We show here that the C-ter domain is responsible for the uptake of Amblyomin-X by tumor cells and highlight the ability of this domain to deliver intracellular cargo by the strong enhancement of the intracellular detection of molecules with low cellular-uptake efficiency (p15) after their coupling with the C-ter domain. In contrast, the N-ter Kunitz domain of Amblyomin-X is not capable of crossing through the cell membrane but is associated with tumor cell cytotoxicity when it is microinjected into the cells or fused to TAT cell-penetrating peptide. Additionally, we identify the minimum length C-terminal domain named F2C able to enter in the SK-MEL-28 cells and induces dynein chains gene expression modulation, a molecular motor that plays a role in the uptake and intracellular trafficking of Amblyomin-X.